Impacto socioeconômico da covid-19 às famílias em (des)proteção social em Luanda - Jorge, Miguel Pimpão [UNESP]; Fernández, Yadira Arnet [UNESP]; Jacinto, Adriana Giaqueto [UNESP] (Cortez Editora Ltda, 2024)
The objective was to analyze how some families that survive in the informal market were affected by government measures taken during the Covid-19 pandemic in Angola. A bibliographic and documentary research was carried out. The results indicate that the measures taken by the government deepened the situation of poverty of informal workers, since their survival depended on the daily gain from their sales, causing the loss of a large part of formal jobs, causing many women to resort to to informal work in order to guarantee family survival.

Objetivou-se analisar o modo como algumas famílias que sobrevivem do mercado informal foram afetadas pelas medidas governamentais tomadas durante a pandemia da covid-19 em Angola. Realizou-se uma pesquisa bibliográfica e documental. Os resultados apontam que as medidas tomadas pelo governo aprofundaram a situação de pobreza dos trabalhadores informais, uma vez que a sua sobrevivência dependia do ganho diário das suas vendas, provocando a perda de grande parte dos trabalhos formais, fazendo com que muitas mulheres recorressem ao trabalho informal no intuito de garantir a sobrevivência familiar.
Socioeconomic impact of covid-19 on families in social (lack of) protection in Luanda
Keywords: Socioeconomic impact; Covid-19; Social lack of protection; Impacto socioeconômico; Covid-19; Desproteção social